2010
DOI: 10.3727/096368910x508843
|View full text |Cite
|
Sign up to set email alerts
|

Improved Yield and Functional Parameters of Rat Pancreas Islets Isolated under Intramuscular Anesthesia

Abstract: Intraperitoneal (IP) anesthesia is commonly used for laboratory animal experiments including rat islet isolation. However, the direct effects of anesthetics on pancreatic islets have been neglected. This study compared the islet function and recovery yield from rats that were anesthetized using IP and intramuscular (IM) injection. In addition, the lag time required to lose deep pain was measured in the following anesthetics combinations. Lewis rats were anesthetized using ketamine and xylazine (K/X) or zoletil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…Obtaining a higher mean islet mass from a pancreatic graft is crucial for a successful outcome in the islet isolation procedure (7,25). Although several methods for obtaining a higher islet mass have been reported (12), the optimal timing at which to terminate the collagenase digestion and start dilution usually depends on the appearance and number of islets in the serially digested samples (4,13,25). Further objective parameters are therefore needed to determine the digestion termination point and promote successful outcomes (4).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Obtaining a higher mean islet mass from a pancreatic graft is crucial for a successful outcome in the islet isolation procedure (7,25). Although several methods for obtaining a higher islet mass have been reported (12), the optimal timing at which to terminate the collagenase digestion and start dilution usually depends on the appearance and number of islets in the serially digested samples (4,13,25). Further objective parameters are therefore needed to determine the digestion termination point and promote successful outcomes (4).…”
Section: Discussionmentioning
confidence: 99%
“…However, it is still difficult to recover the entire quantity of islets contained in a pancreas (16). Given that islet isolation is crucial for the success of this transplantation procedure, many attempts to obtain more viable islets have been reported in the literature (1,12,18). In rodent models, collagenase digestion can be performed for a specific period of time to obtain a peak islet yield; however, in humans, the timing of dilution is empirically determined by human expertise and experience (1,1618).…”
Section: Introductionmentioning
confidence: 99%
“…Rat islets appear to provide greater challenge, as there appears to be greater variance in yield between strains, ages and condition of donor rats 33,34 . Overall, the approach of intra-ductal inflation and sheer-force disruption of the digested tissue are consistent with mouse protocols.…”
Section: Primary Isletsmentioning
confidence: 99%
“…Diabetes continued to be a major focus with three papers evaluating different aspects of islet transplantation. Ikemoto et al (4) looked at islet quality following international shipping, while Kim et al (8) reported on the improved yield and functional parameters of rat pancreas islets under intramuscular anesthesia. Noguchi et al (18) compared modified Celsior solution and M-Kyoto solution for human pancreas preservation.…”
mentioning
confidence: 99%